Corrosion inhibition, adsorption and thermodynamic properties of hydrophobic-tailed imines on carbon steel in hydrochloric acid solution: a comparative study - Mohd, Noor Khairin; Yeong, Shoot Kian; Ibrahim, Nor Azowa; Mohd Nor, Siti Mariam; Wan Yunus, Wan Md. Zin; Ghazali, Mariyam Jameelah; Lim, Wen Huei (Taylor and Francis, 2021)
Three hydrophobic-tailed imine compounds containing linear alkyl, branched alkyl and phenyl groups adjacent to the imine bond namely N-propylidenehexadecanehydrazide (PHH-L), N'-(2,2-dimethylpropylidene)hexadecanehydrazide (DMPHH-B) and N-phenylpropionalidene hexadecanehydrazide (PPHH-A), respectively were successfully synthesized with good yields and high purity. Inhibition properties were evaluated with the corrosion of carbon steel in 1 M HCl solution by electrochemical measurements and scanning electron microscopy-energy dispersive x-ray (SEM-EDX). Potentiodynamic polarization measurement indicates that the synthesized inhibitors were effective mixed-type inhibitors and adsorbed on the carbon steel surface following the Langmuir adsorption isotherm with the free energy of adsorption, ΔGoads values ranging from −37.9 kJ mol−1 to −39.5 kJ mol−1 by mixed absorption involving both physisorption and chemisorption. Impedance spectroscopic analysis revealed that the inhibitors reduced the corrosion process by a charge-transfer process. SEM-EDX analysis revealed that the corrosion damage of the carbon steel surface was reduced in the presence of the inhibitors containing linear alkyl (PHH-L) and phenyl (PPHH-A) groups. In contrast, DMPHH-B, a compound with a branched alkyl group increased corrosion damage.